Public opinion on corruption in Sabah : a case in Kota Kinabalu and Tambunan / Elvera Dorotheus and Khatijah Rasid - Dorotheus, Elvera; Rasid, Khatijah (2015)
In the last previous decades, corruption turns into one of the huge issue arise which all governments regardless of any level of government will have to deal with. Previous researchers had mentioned that good governance plays important role in the country's development and the most important thing is it requires the highest standard of integrity, openness and also transperancy. As indicated by John Healey and Mark Robinson, they expressed that good governance indicates a high level of organisational effectiveness in relation to a policy formulation in financial approach and its commitment to development, steadiness and populace welfare. Corruption is a complex phenomenon and it covers a broad range of human actions. According to the World Bank definition, corruption may be defined as the abuse of public office for private interest or also called as private gains. It happen when an officials accepts or solicits a bribe. It is also abused when private agents try to offer bribes to the public officer for competitive advantage and for the purpose of profit.